Local buckling resistances of cold-formed high-strength steel SHS and RHS with varying corner radius. (March 2022) - Yang, Lu; Yin, Fei; Wang, Jie; Bilal, Azrat; Ahmed, Ari Habeeb; Lin, Manfang
Abstract: This paper reports an experimental and numerical study of the cross-sectional behaviour of cold-formed high-strength steel (HSS) square and rectangular hollow section (SHS and RHS) members. Six stub column tests, six 3-point and three 4-point bending tests have been carried out, followed by the development of accurate finite element (FE) models and a parametric study. Based on the test and FE results, the design rules for slender cross-sections in European, American, Australian and Chinese standards and the GSRM method have been assessed via reliability analyses. A new equation for deriving the cross-sectional slenderness of SHS and RHS considering the influence of corner radius and new area reduction factors for designing slender cold-formed S900 (and above) SHS and RHS have also been proposed. Highlights: A testing programme comprising of tensile tests, geometric imperfection measurement, stub column tests and bending tests. A numerical parametric study considering extended steel grades and various cross-sectional geometries. Current standards assessed via reliability analyses. GSRM extended to cover the design of cold-formed HSS cross-sections with steel grades above S900. New hand-calculation method for deriving cross-sectional slenderness considering the effect of corner radius.